Investigation of dual-energy X-ray photon counting using a cadmium telluride detector with dual-energy selection electronics. (January 2017) - Sato, Eiichi; Kosuge, Yoshiyuki; Yamanome, Hayato; Mikata, Akiko; Miura, Tatsuya; Oda, Yasuyuki; Ishii, Tomotaka; Hagiwara, Osahiko; Matsukiyo, Hiroshi; Watanabe, Manabu; Kusachi, Shinya
Abstract: To obtain two kinds of tomograms at two different X-ray energy ranges simultaneously, we have developed a dual-energy X-ray photon counter with a cadmium telluride (CdTe) detector and two energy-selecting devices (ESDs). The ESD consists of two comparators and a microcomputer (MC). X-ray photons are detected using the CdTe detector, and the event pulses from a shaping amplifier are sent to two ESDs simultaneously to determine two energy ranges. X-ray photons in the two ranges are counted using the MCs, and the logical pulses from the MCs are input to frequency-to-voltage converters (FVCs). The outputs from the two FVCs are input to a personal computer through an analog-to-digital converter to carry out dual-energy computed tomography. The tube voltage and current were 80 kV and 8.5 μA, respectively. Two tomograms were obtained simultaneously with two energy ranges. K-edge CT using iodine and gadolinium media was carried out utilizing two energy ranges of 33–45 and 50–65 keV, respectively. The maximum count rate was 6.8 kilocounts per second with energies ranging from 10 to 80 keV, and the exposure time for tomography was 9.8 min. Highlights: X-ray counter based on two energy-range selecting devices has been constructed. Each device is realized by two comparators and a microcomputer. Photon energy determination was carried out online using microcomputers. CT was performed for two X-ray energy ranges. Iodine and gadolinium K-edge CT was accomplished simultaneously.